2016
DOI: 10.1111/asj.12587
|View full text |Cite
|
Sign up to set email alerts
|

Length of winter coat in horses depending on husbandry conditions

Abstract: This paper analyzes changes in the length of coat on selected body areas in horses and ponies kept under different husbandry (stable) conditions during the winter-spring period. The study included 12 Małpolski geldings and 12 geldings of Felin ponies aged 10-15 years. Horses were kept in two stables (six horses and six ponies in each stable). The type of performance, husbandry conditions and feeding of the studied animals were comparable. As of December 1, samples of hair coat from the scapula, sternum, back a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…The mean hair length was found to be 2.4 cm, regardless of horse breed type or sampling month. This correspond well to the findings of Bocian et al (2017). The mean hair length and length of the longest hairs in the present study were significantly longer in CB than in WB breed types.…”
Section: Hair Coat Characteristicssupporting
confidence: 93%
See 1 more Smart Citation
“…The mean hair length was found to be 2.4 cm, regardless of horse breed type or sampling month. This correspond well to the findings of Bocian et al (2017). The mean hair length and length of the longest hairs in the present study were significantly longer in CB than in WB breed types.…”
Section: Hair Coat Characteristicssupporting
confidence: 93%
“…The length of hair in healthy horses is influenced by season (number of daylight hours) and temperature. Also, genotype, quality and quantity of feed and human management system (blanketing, stabling) will affect the hair coat properties of individual horses (Cymbaluk and Christison, 1989;Bocian, et al, 2017).…”
Section: Individual Differencesmentioning
confidence: 99%
“…This process aims to adjust the body temperature to the environmental conditions. A complete change of the summer coat to a winter coat should take place during late autumn [39]. From August until January, the hair growth rate increased, indicating a greater overall length during late autumn and early winter.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed a hair growth rate of 0.66 ± 0.11 cm/month on average in the ventral abdominal area. Different factors affect the seasonal coat shedding, including the season, genetic background, type of feeding, and housing systems [37][38][39]. This process aims to adjust the body temperature to the environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…method feeding use (blanketing, etc.) (Cymbaluk and Christison 1989, Dunnet 2005, Bocian et al 2017.…”
Section: Discussionmentioning
confidence: 99%